Analisis Kenyamanan Ruang Parkir Kampus Institut Teknologi Mitra Gama - Pras, Adi Prastya; Yusno, Zaharani; Ramli, Wan; Arvin, Arvin; Apriadi, Apriadi (SAINSTEK, 2024)
This research aims to analyze parking comfort on the ITMG Campus. Aspects analyzed include the availability of parking spaces, parking management systems, and user perceptions of parking comfort. Data was obtained through direct surveys, interviews and field observations. The research results show that parking availability remains a challenge, with some areas full during peak hours. The parking management system is considered quite good but requires improvements in monitoring and security aspects. In conclusion, parking comfort on the ITMG Campus can be improved through additional parking spaces, the use of technology, and increased security.